2014
DOI: 10.1590/1678-457x.6452
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the concentrations of maltogenic α-amylase and fat on the technological and sensory quality of cakes

Abstract: The characteristics that define cake quality can be improved by the use of adequate ingredients and a correct balance of the formulation. Fat is used for its effect on softness and because it imparts flavor and calories. Enzymes such as maltogenic α-amylase can also have a positive effect on cake texture during storage by decreasing amylopectin re-crystallization and thus delaying starch retrogradation providing longer-lasting crumb softness. The objective of this study was to determine the effect of different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 23 publications
0
15
1
Order By: Relevance
“…The reference batter recipe was a pound cake recipe adapted from ( Table 1 ) [ 27 ]. The four cake formulations containing the different types of fat, namely E1, E2, E3, and the palm oil were prepared using a Kitchen Aid mixer (Professional 600 6 QT; St. Joseph, MI, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reference batter recipe was a pound cake recipe adapted from ( Table 1 ) [ 27 ]. The four cake formulations containing the different types of fat, namely E1, E2, E3, and the palm oil were prepared using a Kitchen Aid mixer (Professional 600 6 QT; St. Joseph, MI, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The pH value of the cake batter was determined using a pH meter (model 827; Metrohm, Switzerland). For the pH measurement, 10 g of cake batter was diluted in 100 mL of distilled water at 25 °C [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Courtin and Delcour (2002) reported higher bread scores for enzyme supplemented breads as compared with control. In addition, Bedoya et al (2014) confirmed that the cakes fortified with maltogenic amylase showed the highest score for the attribute appearance, which influenced consumer purchase intention.…”
Section: Sensory Analysismentioning
confidence: 63%
“…The presence of these gas holes could have a great influence on the physical properties of made cakes such as density and water holding capacity. As explained by Bedoya et al (2014), cakes added with maltogenic amylase remained in a positive way, in terms of appearance. The same results were obtained by El Abed et al ( 2017) since the addition of amylase from parthenocarpic date caused a more open crumb grain, cohesive dough and internal resistant structure, thus resulting in better gas retention capacity.…”
Section: Observations Of Cakesmentioning
confidence: 76%